Perancangan Aplikasi Sistem Informasi Barang Berbasis Android Pada PT. Quantum Mitra Sinergi - Albert Anotona Hary Saputra Gulo (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2021)
In this technological era, almost all companies use technology development as a tool to develop their companies and businesses. PT. Quantum Mitra Sinergi is one of the companies engaged in the IT field that requires a tool that can help workers keep a list of incoming and outgoing items. One tool that can help workers is through mobile devices. This device can be an inventory system for companies. In this case the system is expected to help workers in listing the list of goods in and out of and into the company's warehouse. The method used in this study is the System Development Life Cycle method, which starts from the needs analysis, system design, coding and testing. The purpose of this research is to assist workers in storing goods properly through the application system that will be built. As a result, the design of an inventory system application at PT. Quantum Mitra Sinergi with Android-based that can be used on smartphones, and with the barcode scan feature using a smartphone camera, workers can record items that want to enter and exit goods storage with more flexibility and faster, system design built with two different systems namely Android and also the Web.